Ellagitannins and Their Derivatives: A Review on the Metabolization, Absorption, and Some Benefits Related to Intestinal Health - Erick M. Raya-Morquecho; Pedro Aguilar-Zarate; Leonardo Sepúlveda; Mariela R. Michel; Anna Iliná; Cristóbal N. Aguilar; Juan A. Ascacio-Valdés (Microbiology Research)
Ellagitannins are bioactive phenolic acids found in various fruits, plants, and beverages such as wine and spirits. This review aims to discuss the metabolism, absorption, and some health benefits related to the intestinal activity of these molecules, as well as some supplements developed from them. Ellagitannins are first biodegraded to ellagic acid and then to urolithins, which are more easily absorbed. This process is mediated by specific enzymes and intestinal microbiota. Not all individuals can metabolize ellagitannins into urolithins due to differences in the composition of the intestinal microbiota, resulting in three phenotypes: metabotypes A, B, and 0. In recent decades, ellagitannins and their derivatives (ellagic acid and urolithins) have gained significant attention for their potential benefits against various digestive diseases, including irritable bowel syndrome, peptic ulcers, gastritis, colon cancer, esophageal cancer, and pancreatic cancer. As a result, nutraceutical supplements have been developed to treat these conditions, representing significant and promising applications of these compounds in digestive health.